Charles Julius Allen and Grace Elizabeth Allen papers - Allen, Charles Julius, 1840-1915.; Allen, Grace Elizabeth, 1886-1976.
Correspondence, diaries, family history, personal reminiscences, notes, clippings, and printed matter chiefly of Charles Julius Allen and his daughter, Grace Elizabeth Allen. Papers of Charles Julius Allen relate to his life as a cadet at the United States Military Academy, West Point (1860-1864) and to his service in the U.S. Army Corps of Engineers, especially during the Civil War at Mobile Bay, Ala. Papers of Grace Elizabeth Allen consist chiefly of eighty-three diaries kept throughout her life. They include references to her service with the American Association of the Red Cross; to Washington, D.C., and New York social life; to her travels; and to various world, national, and local affairs. Also includes letters to Grace Elizabeth Allen from George S. Patton written during World War II.
Library of Congress Geography and Map Division.
Library of Congress Prints and Photographs Division.
Charles Julius Allen and his daughter, Grace Elizabeth Allen.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Patton, George S. -- 1885-1945 -- Correspondence; Allen family; United States. -- Army. -- Corps of Engineers; American Association of the Red Cross; United States Military Academy; Voyages and travels; World War, 1939-1945.; Alabama -- History -- Civil War, 1861-1865.; Mobile Bay (Ala.) -- History; New York (N.Y.) -- Social life and customs; United States -- History -- Civil War, 1861-1865.; Washington (D.C.) -- Social life and customs